Congenital Upper Eyelid Coloboma: Clinical and Surgical Management - José María Ortega Molina; Eduardo Ramón Mora Horna; Andrés David Salgado Miranda; Rosa Rubio; Ana Solans Pérez de Larraya; Guillermo Salcedo Casillas (Case Reports in Ophthalmological Medicine)
Purpose. The goal was to describe our experience in the surgical management and treatment of four patients with congenital upper eyelid colobomas. Methods. A descriptive, observational, retrospective study was performed including patients with congenital eyelid colobomas referred to Asociación para Evitar la Ceguera en México I.A.P. “Dr. Luis Sánchez Bulnes” between 2004 and 2014 and assessed by the Oculoplastics and Orbit Service. Results. The four cases required surgical treatment of the eyelid defects before one year of age and their evolution was monitored from the time of referral to the present day. One of the patients needed a second surgical procedure to repair the eyelid defect and correct the strabismus. Conclusions. Eyelid colobomas are a potential threat to vision at an early age, which requires close monitoring of the visual development of patients.